Guiding social media use: proposed values and the role of Maqasid al-Shari‘ah - Shompa, Zohora Azmin; Saidin, Aznan Zuhid; Hussin, Husnayati; Muhammad, Muhd. Rosydi; Abu Bakar, Elistina (IEEE Xplore, 2018)
The use of social media has created a challenging situation in terms of the content and communications that is made available on the social media platforms. This includes various issues like accuracy, privacy, security, respect, dignity and many others. A main aspect of handling these challenging issues lies in the person using the social media. Some values for the user of social media are proposed as a way of guiding their actions in communicating and providing content online. The values were obtained through a focus group discussion consisting of several academics and experts. Reference is also made to the Maqasid al-Shari‘ah (objectives of Islamic law) from the literature to suggest several principles for the social media user. This provides a discussion from an Islamic perspective on managing the challenges in using social media.